Radiological examination of impact of edentulism on the articular eminence inclination using orthopantomogram - Modgi, Chetan; Awari, Karishma; Rajani, Priyal; Palaskar, Jayant; Jadhav, Prashant; Vinay, Vineet (Journal of Orofacial Research, 2020)
Background: Occlusion is an important component of the temporomandibular joint (TMJ). Little is known about the association between missing teeth and TMJ changes. The objective of this study was to compare inclination of the articular eminence (AE) between dentulous and edentulous arch. Method: A total of 500 patients were divided into group A (dentulous) and group B (edentulous). Group B was further divided into subgroups based on years of edentulism into group 1, group 2 and group 3. On patient’s panoramic radiograph, the sagittal outline of the AE and glenoid fossa were traced, and a sagittal condylar path inclination was constructed by joining the crest of the glenoid fossa and the crest of AE. This was then related to the constructed Frankfurt’s horizontal plane to determine the inclination of AE. Results: The mean measured value for the AE inclination was varying with all the groups. The mean and standard deviation value (combining right & left) for Group A was 42.8+/-6.83 degrees, Group B was 30.45+/-6.55degrees, Group 1 was 30.2+/-7.23degrees, Group 2 was 31.2+/-4.75 degrees, and Group 3 was 27.5+/-9.3 degrees. Significant differences were found in AE inclination between the dentulous and edentulous groups (P